2015
DOI: 10.1039/c4nr07359b
|View full text |Cite
|
Sign up to set email alerts
|

The unexpected non-monotonic inter-layer bonding dependence of the thermal conductivity of bilayered boron nitride

Abstract: Hexagonal boron nitride (BN) and its bilayer form are very fascinating two-dimensional materials that have attracted tremendous interest recently. Their realistic applications in emerging nanoelectronics usually quest for manipulating the thermal transport properties in a precise manner. Using nonequilibrium molecular dynamics simulations, we herein studied the effect of inter-layer covalent bonding on the thermal conductivity of bilayered BN. We found that the in-plane thermal conductivity of bilayered BN, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…Thus, it can be concluded that the redshi of the phonons with high frequency results in the low thermal conductivity of Si/Ge hetero-twinned SLs. 29 Besides, the similar PDOS of bulk twinned Si and the single crystal Si can also be observed, which indicates the weak phonon scattering at twin boundaries.…”
mentioning
confidence: 65%
“…Thus, it can be concluded that the redshi of the phonons with high frequency results in the low thermal conductivity of Si/Ge hetero-twinned SLs. 29 Besides, the similar PDOS of bulk twinned Si and the single crystal Si can also be observed, which indicates the weak phonon scattering at twin boundaries.…”
mentioning
confidence: 65%
“…where is the wave vector in the first Brillouin zone, ν is the phonon branch, κ α denotes the thermal conductivity in α direction, c ph is phonon volumetric specific heat calculated by , k B is the Boltzmann constant, V is the system volume, υ g,α is α -component of the phonon group velocity, τ is the phonon lifetime. Note that the above phonon SED method has been successfully used by us to perform the phonon mode analysis for a wide variety of nanostructures, e.g., two-dimensional silicene 22 , boron nitride (BN) 14 , and one-dimensional graphyne nanotubes 23 . Other researchers have also investigated the phonon lifetime of graphene using the SED method 24 or an exact numerical solution of the Boltzmann transport equation 25 .…”
Section: Discussionmentioning
confidence: 99%
“…However, in fact, interlayer bonding ( Fig. 1 ) has a complicated effect on the in-plane thermal conductivity of bilayer two-dimensional structures, depending on not only the interlayer bonding density but also the detailed topological configuration of the interlayer bonds 14 .…”
mentioning
confidence: 99%
“…17 Bulk SnSe is especially a robust thermoelectric candidate for energy conversion applications in the low and moderate temperature range due to its anisotropic and low symmetry crystal structure. 1,2 The discovery of graphene leads to an upsurge in exploring two-dimensional (2D) materials, [18][19][20][21] such as hexagonal boron nitride (h-BN), germanene, silicene, transition metal dichalcogenides (TMDCs) and phospho-rene, which have attracted tremendous attention due to their unique dimension-dependent properties. 22 In addition to the currently available 2D materials, 2D SnSe has been recently synthesized, which is greatly expected to be potential in the applications as photodetector, photovoltaic, piezoelectric and thermoelectric devices.…”
Section: Introductionmentioning
confidence: 99%